Manipulating energy migration in nanoparticles toward tunable photochromic upconversion - Jinshu Huang; Langping Tu; Haozhang Huang; Haopeng Wei; Qinyuan Zhang; Bo Zhou (Nature Communications)
Abstract Smart control of energy interactions plays a key role in manipulating upconversion dynamics and tuning emission colors for lanthanide-doped materials. However, quantifying the energy flux in particular energy migration in the representative sensitizer-activator coupled upconversion system has remained a challenge. Here we report a conceptual model to examine the energy flux in a single nanoparticle by designing an interfacial energy transfer mediated nanostructure. We show that energy migration indeed occurs simultaneously with energy transfer in a sensitizer-activator system and the competition between them can be quantified by proposing a characteristic ratio parameter. Moreover, this model is also able to realize the color-switchable photochromic upconversion by temporal control of up-transition processes. These findings offer a deep insight into the understanding of upconversion dynamics and provide a versatile approach to manipulating the energy flux in nanostructures with tunable emission colors, showing great promise in applications of logic operation and information security.